(untitled) (Revista Direitos Humanos e Democracia, 2025)
His article presents some results of post-doctoral research in Law funded by the Dean of Inclusion and Belonging at the University of São Paulo (PRIP USP). It addresses the field of Law and Ethnic-Racial Relations and its relationship with anti-racist legal education. In this sense, we highlight that although the field has existed for more than 40 years in Brazil, it was only after the more consistent implementation of policies to promote racial equality that more systematic studies in the field have been developed. But, there is still a lot to be done. The new DCNs for the 2018 Bachelor of Law courses open up a space for important dialogue between the field of Law and Ethnic-Racial Relations and Anti-Racist Legal Education, which can enable the consolidation of both areas in an autonomous and consistent manner. . Our method is historical-legal, with analysis of dissertations and theses and uses theoretical references produced by black and black jurists.